Economic analysis of vegetable crop production: A study with family farmers - Socoloski, André; Grzebieluckas, Cleci; dos Santos, Josiane Silva Costa; Stieler, Marinez Cargnin [UNESP]; de Lima, Aparecida de Fátima Alves (My University, 2017)
Family farming is distinguished by the diversity of food supplies and also the creation of jobs in rural areas. In the management it is essential to know the costs and returns effectively gain in activity. The aim of this study is to make an analysis of economic viability of tomato, lettuce and sweet potato production in two properties of family farmers in Tangará da Serra – MT municipality. It is a descriptive research with a quantitative approach and had as analysis tools the Net Present Value (NPV), Internal Rate of Return (IRR), the Capital Return Time (Payback) and Cost Benefit Analysis (CBA). The Minimum Rate of Attractiveness (MRA) was 1.11 % per month. The analysis was the analysis was performed based on a hectare of land and with different scenarios for the period of one year. The collection instruments were structured script, semi structured interviews and direct observation. The results shows that all crops are economically viable, especially the lettuce crop, which exceeded the NPV and IRR of tomato and sweet potato, cultivation and the culture of sweet potato proved to be most sensitive to revenue changes and costs.
Keywords: Costs; Family farming; Foods; Return